Contribuição de machos suínos para paternidade de leitões gerados por inseminação artificial heterospérmica - Ferreira, Carlos Eduardo Ranquetat (2013)
The common use of pooled sperm doses (composed of sperm of two or more boars) in artificial insemination (AI) in swine limits the precise evaluation of individual boar fertility. Thus, marginal differences in potential fertility among boars are clouded by the use of heterospermic AI. This study had the objective of identifying the contribution of individual boars for the paternity of progeny generated by heterospermic AI. Four boars were used as sperm donors (A, B, C and D). After collection, ejaculates from those boars were used to compose homospermic and heterospermic doses (AB, AC, AD, BC, BD and CD), all including 3.0 x 109 spermatozoa in 80 ml. A total of 511 females were inseminated. The paternity of 4.119 piglets was determined through the use of SNP (Single nucleotide polymorphism) markers : 3.558 from heterospermic AI; and 461 from homospermic AI. The comparison of paternity per pool showed that the pool AC was the only one in which each boar contributed similarly for paternity (P > 0.05), whereas differences between boars occurred in all other pools (P < 0.05). The greatest contribution for paternity of piglets occurred for boar D, which sired nearly 60% of all piglets boar in the pools in which that boar took part. These results indicate that in most of the heterospermic AI, individual boars contribute distinctly for the paternity of the piglets, even though each boar contributes with the same sperm concentration in the pooled sperm doses. Key